Giant Cell Granulomas of Jaws: a Clinicopathologic Study - Shruti Gupta; Anjali Narwal; Mala Kamboj; Anju Devi; Anita Hooda (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of present study was to investigate and correlate the histological findings in central giant cell granuloma and peripheral giant cell granuloma of jaws with clinical and radiographic interpretations of the lesion.